2000
DOI: 10.1088/0953-8984/12/10/310
|View full text |Cite
|
Sign up to set email alerts
|

Neutron powder diffraction study of the RFe11.5Ta0.5(RequivLu, Er, Ho, Dy and Tb) compounds

Abstract: We report a systematic study of the crystallographic and magnetic structures of the RFe11.5 Ta0.5 (R Lu, Er, Ho, Dy and Tb) compounds carried out by means of neutron powder diffraction. Thermal dependencies of lattice parameters, magnetic moments and magnetization directions have been determined. The hierarchy of the Fe magnetic moments at the 8i, 8j and 8f sites was found to be µ8i >µ8j µ8f for all compounds at all temperatures. The influence of the atomic environments on the strength of the Fe local mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 22 publications
6
27
0
Order By: Relevance
“…Based on the similarity to DyFe 12jx T x with T = Nb [6], T = Ti [9], and T = W [10], the anomalies can be ascribed to the effects of spin reorientation. With decreasing temperature from room temperature (as confirmed by neutron powder diffraction measurement [3]), the easy magnetization direction of the DyFe 12jx Ta x compounds changes from easy axis at T sr1 , via an easy-cone range, to easy plane at T sr2 .…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Based on the similarity to DyFe 12jx T x with T = Nb [6], T = Ti [9], and T = W [10], the anomalies can be ascribed to the effects of spin reorientation. With decreasing temperature from room temperature (as confirmed by neutron powder diffraction measurement [3]), the easy magnetization direction of the DyFe 12jx Ta x compounds changes from easy axis at T sr1 , via an easy-cone range, to easy plane at T sr2 .…”
Section: Resultsmentioning
confidence: 81%
“…Recently, Piquer et al [2,3] reported that the Ta-stabilized phase of RFe 11.5 Ta 0.5 only forms with the heavier rare-earth elements Tb, Dy, Ho, Er and Lu. Vert et al [4] found that pure singlephase samples do not form but that all samples included !-Fe and/or Fe 2 Ta as impurity phases and approximately single phase samples of RFe 12 j x Ta x were stabilised for x = 0.5-0.7 [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interest in having as small an amount as possible of the third element, critical for the stabilization of the iron-rich phase with ThMn 12 -type structure, lies in the avoidance of the severe decrease in the Curie temperature and iron magnetization when increasing the M metal concentration to the upper limit of its solubility range [5,6]. However, up to the present only a few RFe 12−x M x systems are known which comply with this requirement; they form for M = Ta (x ≈ 0.5-0.7) [7][8][9][10], Nb (x ≈ 0.6-0.7) [11][12][13][14][15][16], and W (x ≈ 0.7) [17]. Apparently, the compounds with the highest iron content form when M is a 4d or 5d element, and particularly, with rare earths from Tb to Ho.…”
Section: Introductionmentioning
confidence: 99%